Melonhead and the big stink - Kelly, Katy (Delacorte Press, 2010)
During the summer between fourth and fifth grade, Adam "Melonhead" Melon, who lives in the Washington, D.C., neighborhood of Capitol Hill, tries to stay out of trouble to earn a trip to New York City to see the giant "stink flower."